2010
DOI: 10.3813/aaa.918314
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Skewness in Violin Bowing: Should the Bow be Straight or Not?

Abstract: Bowing parallel to the bridge is by manyplayers considered as the golden standard. However, in practice straight bowstrokes are rarely observed, and the bowcan be considerably slanted even in the performance of renowned players. In anyc ase, the angle of the boww ith the violin (skewness)i sl ikely to form an important control parameter,which has hardly been addressed in scientificstudies of violin performance. In the current study measurements of skewness in violin and viola performance are presented, and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…With differential slippage, bow hair release is not uniform as differences exist between the inner and outer edges of bow hair – then at extreme angles these temporal differences will be magnified to an even greater degree, as one side of the bow will be significantly further from the bridge than another (Askenfelt, 1988; Chafe, 1988; McIntyre et al, 1981). An alternative interpretation of noise production at extreme angles is that, by keeping the bow placement constant, the player opposes the natural drift of the bow that occurs under influence of the stick-slip interaction with the string, and by this interferes with the Helmholtz motion (Guettler, 2003; Schoonderwaldt, 2010). For bow placement, movement from tasto 1 to tasto 3 produced tones with progressively lower HNR values, however, from tasto 3 to tasto 5, we find a mirror effect with rising HNR values.…”
Section: Resultsmentioning
confidence: 99%
“…With differential slippage, bow hair release is not uniform as differences exist between the inner and outer edges of bow hair – then at extreme angles these temporal differences will be magnified to an even greater degree, as one side of the bow will be significantly further from the bridge than another (Askenfelt, 1988; Chafe, 1988; McIntyre et al, 1981). An alternative interpretation of noise production at extreme angles is that, by keeping the bow placement constant, the player opposes the natural drift of the bow that occurs under influence of the stick-slip interaction with the string, and by this interferes with the Helmholtz motion (Guettler, 2003; Schoonderwaldt, 2010). For bow placement, movement from tasto 1 to tasto 3 produced tones with progressively lower HNR values, however, from tasto 3 to tasto 5, we find a mirror effect with rising HNR values.…”
Section: Resultsmentioning
confidence: 99%
“…The contact surface is then reduced to the touching points of perpendicular cylinders, where friction occurs on the same materials all along the bow length, and the process is repeated many times without disturbing the emerging sound. Previous studies have shown that only a few mechanical parameters determine this tune: skewness angle, maximum bow velocity, drift velocity (or bow–bridge distance dependence), bow position, tilt, inclination, and bow force [911] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%